Seizures, electroencephalographic abnormalities, and outcome of ischemic stroke patients - Bentes, Carla (2020)
© 2017 The Authors. Epilepsia Open published by Wiley Periodicals Inc. on behalf of International League Against Epilepsy. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial, and no modifications or adaptations are made.